Analisis Literasi Digital Terhadap Pemahaman Nilai-Nilai Pancasila pada Mahasiswa Generasi Z di Provinsi Banten - Muhammad Fauzi Rais Lutfi; Siti Rukoyah; Iryanti Asdra; Puput Maelani; Gabriela Kenya; Amanda Ayu Kholidjah Siregar; Alya Bela Syadzwina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The development of information technology has had a major impact on how Generation Z students in Banten obtain information. This situation requires digital literacy skills that are not only technical in nature, but also involve critical thinking and digital ethics. The purpose of this study is to explore the relationship between digital literacy and understanding of Pancasila values among Generation Z students in Banten, as well as to identify factors that support, hinder, and strategies to strengthen Pancasila-based character in the digital world. The method used in this study is qualitative with a literature study approach supported by observations on campus and interviews with students. The findings show that students' digital literacy is in the good category, but it is not yet fully in line with their understanding of Pancasila values. The impact of negative information, such as hoaxes and hedonistic culture, is a major obstacle to national character. Supporting factors include the role of stakeholders in providing space for learning media ethics. This study highlights the importance of integrating Pancasila values into digital literacy through an adaptable Pancasila Education curriculum, the development of educational content, and collaboration between stakeholders. The implications of this study indicate the need to strengthen students' character so that they can become ethical, responsible digital citizens who reflect the values of Pancasila.